Pengembangan Lembar Kerja Peserta Didik Berbantuan Aplikasi PhET Simulation Pada Materi Asam Basa - Windasari Windasari; Kartini Rahman Nisa; Nurhadyati Nurhadyati (Educational Journal, 2026)
This study aims to develop and determine the practicality of developing student worksheets assisted by the PhET simulation application on acid-base material in class XI of SMA Negeri 1 Talibura based on assessments from material experts, media experts, and students. The method used in this study is Research and Development (R&D) with the development stages of the RDR model (Research, Development, Research), while the data collection technique in this study uses questionnaires for material expert validation, media expert validation, and student responses. The developed media was tested by 29 students. The student worksheets assisted by the PhET simulation application on acid-base material for class XI at SMA Negeri 1 Talibura obtained an average score from media experts of 86.45% with a very feasible category, and material experts received an average score of 89.77% with a very feasible category, while student responses to the learning media obtained an average score of 86.27% with a very feasible category. Based on the research data obtained, it can be concluded that the use of student worksheets assisted by the PhET simulation application on acid-base material in class XI at SMA Negeri 1 Talibura is suitable for use in learning activities.